PERANCANGAN ZINE SEBAGAI UPAYA REVITALISASI TRADISI BALIAK KA SURAU DIKOTA PAYAKUMBUH: DESIGNING A ZINE AS AN EFFORT TO REVITALIZE THE BALIAK KA SURAU TRADITION IN PAYAKUMBUH CITY - Ibnu Assadiqha; Taufiq Wahab; Diani Apsari (Universitas Trisakti, 2025)
Designing A Zine As An Effort To Revitalize The Baliak Ka Surau Tradition In Payakumbuh City. Formal education, urbanization, and the gradual decline of oral traditions have reduced the role of the Surau as a traditional educational center in Minangkabau, causing its cultural values to fade over time. Since the 16th century, the Surau has served not only as a place of worship but also as a center for character formation, religious education, customary teaching, and the development of social skills among the younger generation. Payakumbuh City, as a representation of Minangkabau society, reflects the weakening of Surau culture amid modernization and lifestyle changes, which has led to a growing disconnection of youth from their cultural roots. This research aims to design an alternative medium in the form of a zine entitled Tradisi Baliak Ka Surau as an effort to revitalize and reintroduce Surau values to young audiences, particularly adolescents aged 17–25 years in Payakumbuh. The study applies a qualitative approach through observation, literature review, interviews, and questionnaires, with data analyzed using matrix comparison. The results indicate a significant need for alternative media that can reconnect young people with Minangkabau culture through communicative, modern, and audience- relevant visual presentations. The conclusion of this design project highlights the creation of media that is not only visually engaging but also educational, thereby fostering cultural awareness among the younger generation to preserve Minangkabau heritage, starting from the smallest social unit, the family.